2022
DOI: 10.1186/s42523-022-00220-w
|View full text |Cite
|
Sign up to set email alerts
|

Low microbiome diversity in threatened amphibians from two biodiversity hotspots

Abstract: Microbial diversity positively influences community resilience of the host microbiome. However, extinction risk factors such as habitat specialization, narrow environmental tolerances, and exposure to anthropogenic disturbance may homogenize host-associated microbial communities critical for stress responses including disease defense. In a dataset containing 43 threatened and 90 non-threatened amphibian species across two biodiversity hotspots (Brazil’s Atlantic Forest and Madagascar), we found that threatened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It is also known that Bd infection can modify the structure of the bacterial communities of the skin, indicating a potential ecological co‐regulation (Jani et al., 2017 ; Jani & Briggs, 2018 ; Longo et al., 2015 ; Rebollar et al., 2016 ). This bidirectional relationship further highlights the inherent complexities of the host, pathogen, and bacteriome triangle, which, in addition, might be influenced by environmental factors (Greenspan et al., 2022 ; Ruthsatz et al., 2020 ). Although untangling these complex relationships might be difficult in a non‐experimental and non‐manipulative setting, studies in a single host species over a broad geographic scale offer an alternative to tease apart the mechanisms by which the bacterial communities of the amphibian skin are modulated by the individual or interactive influence of host‐specific characteristics, the locality, and geographic factors.…”
Section: Introductionmentioning
confidence: 95%
“…It is also known that Bd infection can modify the structure of the bacterial communities of the skin, indicating a potential ecological co‐regulation (Jani et al., 2017 ; Jani & Briggs, 2018 ; Longo et al., 2015 ; Rebollar et al., 2016 ). This bidirectional relationship further highlights the inherent complexities of the host, pathogen, and bacteriome triangle, which, in addition, might be influenced by environmental factors (Greenspan et al., 2022 ; Ruthsatz et al., 2020 ). Although untangling these complex relationships might be difficult in a non‐experimental and non‐manipulative setting, studies in a single host species over a broad geographic scale offer an alternative to tease apart the mechanisms by which the bacterial communities of the amphibian skin are modulated by the individual or interactive influence of host‐specific characteristics, the locality, and geographic factors.…”
Section: Introductionmentioning
confidence: 95%
“…Martins et al. (2022) found that the Bd‐resistant direct‐developing species Haddadus binotatus has a significantly more diverse and less variable microbiome compared to sympatric susceptible species, indicating that microbiome diversity and stability could be especially important factors for the survival of direct‐developers (Greenspan et al., 2022; Piovia‐Scott et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One leading hypothesis is that drought might cause amphibians to cluster in wet microhabitats, increasing disease transmission to direct-developing species during periods of low rainfall (Burrowes et al, 2004;Longo et al, 2010), but this mechanism may be confounded by species-specific factors. Martins et al (2022) found that the Bd-resistant directdeveloping species Haddadus binotatus has a significantly more diverse and less variable microbiome compared to sympatric susceptible species, indicating that microbiome diversity and stability could be especially important factors for the survival of direct-developers (Greenspan et al, 2022;Piovia-Scott et al, 2017).…”
mentioning
confidence: 99%
“… 16 , 17 Host factors, such as phylogeny, genetics, sex, diet, and age, are well established factors that shape the community structure of host-associated microbiota. 18 , 19 , 20 , 21 , 22 Additionally, environmental factors of microhabitats, including pH, salinity, and particularly the temperature, also contribute to the variations of host-associated microbiota. 8 , 23 , 24 , 25 , 26 , 27 Recently, attention has been paid to the potential association between geographical climate (e.g., annual temperature and precipitation) and microbial variations in wild vertebrates.…”
Section: Introductionmentioning
confidence: 99%